Bacteria‐driven Single‐inlet Microfluidic Fuel Cell with Spiral Channel Configuration. Issue 28 (26th July 2021) - Arun, Ravi Kumar; Sikdar, Nirupam; Roy, Debolina; Chaudhuri, Surabhi; Chanda, Nripen
Abstract: We present a single inlet, spiral‐shaped microfluidic microbial fuel cell (MFC) with porous Paper@Ni anode and Paper@C cathode for energy generation. In the MFC, the anode with a bacterial component is placed along the microchannel side to provide a larger electrode surface area, reduced internal resistance, and enhances mass transport of the 2 % glucose as a substrate for microbial redox reaction. The large electrode area induced by the spiral channel configuration and passive control of the boundary layer enhances the energy output from the fuel cell and eliminates the need for a two‐chambered system. The fuel cell utilizes bacteria Bacillus stratosphericus isolated from mangrove soil to generate bioenergy with an open‐circuit voltage of 0.3 V within 10 seconds. The fuel cell generates a maximum current density of 7 A m −2 and a power density of ∼ 150 mW m −2 . Abstract : A single‐inlet, spiral‐shaped microfluidic microbial fuel cell (MFC) with porous Paper@Ni anode and Paper@C cathode generated energy within 10s using Bacillus stratosphericus as biocatalyst and glucose as substrate. The spiral geometry provides a larger electrode surface area, reduced internal resistance and passive control of the boundary layer to enhance the overall performance.